تطوير تحمل السرعة على وفق فترات راحة مقترحة وتأثيرها في بعض المؤشرات الفسيولوجية وإنجاز ركض مسافة (400) م للشباب - Frag, Farhank (Journal of Physical Education, 2016)
Speed Endurance Development According To Rest Periods And Their Effect On Some Physiological Indicators and 400m Running Achievement In YouthThe aim of the research is to design a training program for speed endurance according to rest periods with heart beats 120, 130, 140 P/M as well as identifying the effect of speed endurance on some physiological variables and 400m running achievement. The researchers used the experimental method. The subjects were (10) youth runners from Al Beshmarka club and Al Slaymania club of the season 2015. The training program was applied according to the proposed rest periods with three training sessions per week for (10) weeks. The results were collected and treated using proper statistical operations. The researchers concluded that the training program helped decrease heart beats of 400m youth runners. In addition to that, they concluded that the program improved the biological control system in muscular cells and the amount of Lactic acid in 400m youth runners. Finally the training program improved the transitional speed endurance and 400m achievement in youth runners.